Framework of Land Value Capture as Financial Solution of Dhaka’s Mass Transit - Haque, Afsana; Rahaman, Md. Mustafizur (The Jahangirnagar Review, 2024)
Land Value Capture (LVC) which is considered as financial mechanism for developed countries infrastructure projects could be a solution of financial burden of operating transit system of a developing city as well. The capital city of Bangladesh is already overburden to provide subsidy on existing public services. Thus, LVC here may be the best strategy for financial solution of operating mass transit and reduce subsidy burden from government. Hence, this study aims to formulate a model for adopting LVC strategy considering empirical investigation on policy and institutional context of Dhaka city. The study based on secondary information and data. Content analysis method has been used to evaluate the available policies and scope for land value capture. Existing institutional context has also been evaluated to come up with an effective LVC framework as the policy implementation and institutional capacity for development management are key underpinning forces for successful LVC. This study suggests joint development and betterment fees as mechanism of LVC. To implement the mechanism RAJUK, DTCA and DCC may be involved in development plan preparation, coordination, and managerial role respectively in one hand. In another hand, DMTCL may implement the plan with private developers. Concurrently, effective link among these institutions via clear guidelines and institutional capacity development may be driving factors of successful implementation of LVC for Dhaka’s mass transit.